PENGARUH HARGA, CITRA MEREK, DAN SOCIAL MEDIA MARKETING TERHADAP MINAT BELI KEMEJA FORMAL PRODUK CARDINAL - Saputra, Muhammad Gilang; Karamang, Ezra (POLITEKNIK LP3I JAKARTA, 2026)
Price, brand image, and social media marketing as they pertain to Cardinal's formal shirt items in Bandung City are going to be the focus of this research. The study takes a quantitative tack by using a descriptive-verificative methodology to measure and analyze the interrelationships of the variables. In order to gather primary data, 105 participants who met the requirements of having bought or shown interest in Cardinal formal shirts and having interacted with the brand's digital marketing efforts were randomly chosen using a purposive sample approach and given a Likert-scale questionnaire. To evaluate the impact of the independent variables on purchase intention, we used multiple linear regression, classical assumption tests, validity and reliability testing, and data analysis. Predicted results show that customers' desire to buy is favorably and considerably affected by a well-planned price strategy, a solid and consistent brand image, and successful social media marketing programs. Cardinal hopes to use the study's strategic findings to improve the efficacy of their marketing, solidify their brand positioning, and maximize their use of social media in order to stay competitive in the ever-changing local fashion business